1996
DOI: 10.1105/tpc.8.9.1519
|View full text |Cite
|
Sign up to set email alerts
|

Apparent redundancy in myb gene function provides gearing for the control of flavonoid biosynthesis in antirrhinum flowers.

Abstract: Two Myb-related transcription factors, Myb305 and Myb340, are expressed specifically in flowers of Antirrhinum. The proteins are structurally very similar throughout their DNA binding domains, implying that they bind to common target motifs. This binding has been demonstrated experimentally. Myb305 has been shown to activate the gene encoding the first enzyme of phenylpropanoid metabolism, phenylalanine ammonia-lyase. We show that Myb340 can also activate transcription from the phenylalanine ammonia-lyase gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
90
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(94 citation statements)
references
References 46 publications
3
90
0
1
Order By: Relevance
“…Molecular genetic studies have frequently shown that there are functional compensation or redundancy among genes with multiple homologs in higher plant species (Pickett and Meeks-Wagner, 1995;Normanly and Bartel, 1999;Bouche and Bouchez, 2001). In certain biological systems, functional interactions among redundant genes have been proposed to fine-tune metabolic activity or growth and development of plant tissues (Moyano et al, 1996;Ferra´ndiz et al, 2000). In line with this thinking, it will be essential to develop mutants lacking the expression of two or more AtPAP genes in Arabidopsis flower in further investigations.…”
Section: Discussionmentioning
confidence: 97%
“…Molecular genetic studies have frequently shown that there are functional compensation or redundancy among genes with multiple homologs in higher plant species (Pickett and Meeks-Wagner, 1995;Normanly and Bartel, 1999;Bouche and Bouchez, 2001). In certain biological systems, functional interactions among redundant genes have been proposed to fine-tune metabolic activity or growth and development of plant tissues (Moyano et al, 1996;Ferra´ndiz et al, 2000). In line with this thinking, it will be essential to develop mutants lacking the expression of two or more AtPAP genes in Arabidopsis flower in further investigations.…”
Section: Discussionmentioning
confidence: 97%
“…The RNA transcript of P-wr is present at a much lower level than that of P-rr in pericarps and cobs (Chopra et al 1996). The deduced amino acid sequence of Myb-p1 exhibits substantial homology to that of MYB305 from snapdragon (Moyano et al 1996). In vivo experiments in yeast, and in vitro binding assays, have shown that MYB305 activates the genes encoding phenylalanine ammonia-lyase and chalcone isomerase by binding to speci®c sites in their promoters.…”
Section: Discussionmentioning
confidence: 96%
“…The proteins MYB305 and MYB340 from snapdragon (Jackson et al 1991) have been shown, both in vivo ± in yeast ± and by an in vitro binding assay, to activate the genes that encode phenylalanine ammonia lyase and chalcone isomerase by binding to speci®c sites in their promoters (Moyano et al 1996). These two MYB genes are assumed to regulate¯avonoid biosynthesis in snapdragon (Sablowski et al 1994;Moyano et al 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the function of only a very small subset of higher-plant R2R3 Myb genes has thus far been elucidated. These functions include the control of cell shape (Noda et al 1994), cell fate (Oppenheimer et al 1991), and cell identity (Waites et al 1998); the regulation of phenylpropanoid (Moyano et al 1996;Sablowski et al 1994),¯avonoid (Grotewold et al 1991;Paz-Ares et al 1987) and tryptophan biosynthesis (Bender and Fink 1998); and the response to hormones (Gubler et al 1995), pathogens (Yang and Klessig 1996) or adverse environmental conditions (Urao et al 1993). Mutations in all plant R2R3 Myb genes so far investigated have very limited phenotypic eects, suggesting that they largely control functions not essential for plant survival or reproduction (Bender and Fink 1998;Grotewold et al 1991;Meissner et al 1999;Noda et al 1994;Oppenheimer et al 1991;Paz-Ares et al 1987;Waites et al 1998).…”
mentioning
confidence: 99%